2017
DOI: 10.15283/ijsc17022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Routes of Injection of Bone Marrow Mesenchymal Stem Cells on Parotid Glands of Rats Receiving Cisplatin: A Comparative Study

Abstract: Background and Objectives: Cisplatin is a powerful antitumor chemotherapeutic agent that is widely used in the treatment of many cancers but it has many side effects on many organs including salivary glands. Bone marrow is considered to be a rich environment that comprises many types of stem cells of which BMSCs (Bone marrow mesenchymal stem cells) are the most studied with potentiality to differentiate into many cell types. This study was conducted to evaluate the effect of different routes of injection of BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(51 reference statements)
3
5
0
Order By: Relevance
“…Histological examination of GI and statistical analysis of acini area % for this group revealed normal acini and acini area% respectively revealed normal acinar. This finding is consistent with previous studies (13) .…”
Section: Discussionsupporting
confidence: 94%
“…Histological examination of GI and statistical analysis of acini area % for this group revealed normal acini and acini area% respectively revealed normal acinar. This finding is consistent with previous studies (13) .…”
Section: Discussionsupporting
confidence: 94%
“…Homogeneous eosinophilic areas were also seen which was in accordance with Eman hany etal (32) (2017). and Mc Innes (33) (2012), the later indicated that these areas, are thought to accumulation of materials which has proteinaceous nature in the tissues (32,33) . While older studies described them as hyaline degeneration (34) .…”
Section: Discussionsupporting
confidence: 88%
“…CT surrounding EDs also seen in group 2 in the present study, also in accordance with Hany et el [9]. and McInnes [30], were described as hyaline degeneration.…”
Section: Homogeneous Hyalinized Areas In Fibroussupporting
confidence: 91%
“…This affects the nucleus leading DNA inhibition and cytotoxic alterations that lead to cell degeneration, desquamation and hyalinization [26]. It can be also be related to the fact that chemotherapeutic drugs can induce reactive oxygen species production leading to increased lipid peroxidation and calcium ions influx which also mediates apoptosis [9]. The epithelial atrophy in the acinar and ductal cells detected in group 2 of our study, obviously observed in the ED lining cells, could also be related to the impaired capacity of cell renewal due to the inhibitory effect of 5-FU on DNA replication and cell mitosis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation